Accelerating Live Single-Cell Signalling Studies. Issue 5 (May 2017) - Cooper, Sam; Bakal, Chris
Abstract : The dynamics of signalling networks that couple environmental conditions with cellular behaviour can now be characterised in exquisite detail using live single-cell imaging experiments. Recent improvements in our abilities to introduce fluorescent sensors into cells, coupled with advances in pipelines for quantifying and extracting single-cell data, mean that high-throughput systematic analyses of signalling dynamics are becoming possible. In this review, we consider current technologies that are driving progress in the scale and range of such studies. Moreover, we discuss novel approaches that are allowing us to explore how pathways respond to changes in inputs and even predict the fate of a cell based upon its signalling history and state. Trends: Major advances in the speed, and ease, with which we can tag proteins, and design reporters for their activity, are driving a surge in live single-cell studies. The throughput of live single-cell studies is currently limited by challenges in tracking and data extraction. Adopting approaches used in multiple object tracking has led to great progress in this area. Live single-cell studies coupled with a range of technologies are allowing us to probe signalling networks, shedding new light upon the dynamics of how cells process information and undertake decisions regarding their fate.